2020
DOI: 10.3389/fmicb.2020.01305
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Dynamics of Pelagic Mycoplanktonic Communities: Interplay of Taxon Abundance, Temporal Occurrence, and Biotic Interactions

Abstract: Marine fungi are an important component of pelagic planktonic communities. However, it is not yet clear how individual fungal taxa are integrated in marine processes of the microbial loop and food webs. Most likely, biotic interactions play a major role in shaping the fungal community structure. Thus, the aim of our work was to identify possible biotic interactions of mycoplankton with phytoplankton and zooplankton groups and among fungi, and to investigate whether there is coherence between interactions and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 108 publications
1
39
0
Order By: Relevance
“…The comparative analysis as PCoA including communities of this study and the one of Banos et al (2020) monitoring mycoplankton communities at Helgoland Roads over a year showed a grouping of samples 20-24 (marine samples) with the samples of Banos et al (2020), while the sample group structure of groups I and II remained intact and well separated from the rest (Supplementary Figure 4).…”
Section: Fungal Community Partitioning and Impact Of Environmental Factorsmentioning
confidence: 71%
See 1 more Smart Citation
“…The comparative analysis as PCoA including communities of this study and the one of Banos et al (2020) monitoring mycoplankton communities at Helgoland Roads over a year showed a grouping of samples 20-24 (marine samples) with the samples of Banos et al (2020), while the sample group structure of groups I and II remained intact and well separated from the rest (Supplementary Figure 4).…”
Section: Fungal Community Partitioning and Impact Of Environmental Factorsmentioning
confidence: 71%
“…Sequences were analyzed with a phylogeny-based approach following the pipeline of Banos et al (2020). Shortly, quality-controlled sequence reads were passed on for classification.…”
Section: Dna Extraction Sequencing and Bioinformaticsmentioning
confidence: 99%
“…The low number of temporally dominant OTUs seems to be a general pattern of mycoplankton communities in coastal environments (Taylor and Cunliffe, 2016; Picard, 2017), where they can peak in abundance several times a year and be categorized according to such patterns (Banos et al ., 2020). The fluctuations can be attributed to a direct or indirect effect of periodically changing environmental conditions, typical of coastal environments (Jeffries et al ., 2016; Taylor and Cunliffe, 2016; Duan et al ., 2018; Banos et al ., 2020). Important factors include periodic transport of water masses with riverine inputs, tidal mixing, wind forcing and sediment resuspension (Tian et al ., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Sequence analysis followed the protocol of Banos et al . (2020). In short, quality controlled reads were aligned to the non‐redundant SILVA SSURef_NR99_132 database (Quast et al ., 2013), using the SINA aligner v.1.2.11 (Pruesse et al ., 2012) in ARB (Ludwig et al ., 2004), with the default settings.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation